Planejamento da paisagem urbana visando a implantação de corredor ecológico entre os dois maiores fragmentos florestais do município de Campinas, a Mata de Santa Genebra e a Mata Ribeirão Cachoeira - Martins, Sabrina Kelly Batista (2023)
Forests in the Atlantic Forest biome are increasingly rare, due to some degration factors that affect forest areas, such as, the uncontrolled urban areas expansion, agricultural and industrial activities, illegal deforestation, animal trafficking and the introduction of exotic species. One of the strategies to reduce the effects of fragmentation, increase the availability of resources and maintain ecological processes is to increase landscape connectivity through recovery actions, aiming to facilitate the flow of organisms among the remnants. Thus, the present study aims to plan the landscape in order to support the implementation of an ecological corridor among the two largest forest remnants of the Municipality of Campinas, the Area of Relevant Ecological Interest Mata de Santa Genebra and the Mata do Ribeirão Cachoeira. Land cover and usage mapping was carried out through visual interpretation of satellite images at a scale of 1:5.000, with the survey being carried out at a scale of 1:2,500, which resulted in a classification of 18 use classes. The species Puma concolor (cougar) was chosen as the target species for developing a connectivity scenario. To construct the corridor proposal, a buffer of 50 meters was created on each side of the chosen connectivity lines, totalizing 100 meters in width. The proposed corridor has an area of 248.86 ha, and taking into consideration the area of the priority remnants that are connected by it, the area adds up to a total of 1.783,49 ha. Validation of the corridor was carried out using trap cameras installed at 5 points along the proposed corridor, with the main species recorded being Puma concolor, Cuniculus paca and Caluromys philander.